The (Possible) End of the Expansion Boom of the Japanese Automobile Industry in Mexico, and the COVID-19 Pandemic - Uchiyama, Naoko (México y la Cuenca del Pacífico, 2023)
The automobile industry is a leading industry in Mexico and thus an engine of its economic growth. In Mexico, Japanese automobile production, as well as the number of Japanese firms, doubled in the last decade amid the Japanese business expansion boom. However, since 2016, after Trump’s election as us President, the expansion boom came to a halt. Simultaneously, the production of Japanese Original Equipment Manufacturers in Mexico, which had reached its peak in 2016, began to decline. This study argues that this sudden production decline before the COVID-19 pandemic was mainly due to the change in consumers’ preference for pick-ups and SUVs in the US market because of the shale oil boom, rather than the so-called “Trump Shock.” It also examines the performances of the automobile industry in Mexico, including those of the Japanese assemblers, during the first two years of the COVID-19 pandemic.